2011
DOI: 10.1177/2042098611406946
|View full text |Cite
|
Sign up to set email alerts
|

No association of maternal vitamin E intake with higher risk of cardiovascular malformations in children: a population-based case–control study

Abstract: Abstract:Objective: In Hungary, vitamin E is frequently used to prevent repeated or threatened abortion. A previous study showed a higher risk of cardiovascular malformations in the children of pregnant women who had a high vitamin E intake either in their diet or by taking supplements. The objective was to examine this association. Methods: The Hungarian CaseControl Surveillance System of Congenital Abnormalities, 19801996, is a large, population-based dataset including 22,843 cases with congenital abnormalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…The doses far exceeding the RDA have not proved to be harmful in previous studies [21], though recently a higher risk of cardiovascular malformations was reported after the high dose of VET in early pregnancy [22]. However, this finding was not confirmed in the population-based Hungarian case-control study [23].…”
Section: Discussioncontrasting
confidence: 53%
“…The doses far exceeding the RDA have not proved to be harmful in previous studies [21], though recently a higher risk of cardiovascular malformations was reported after the high dose of VET in early pregnancy [22]. However, this finding was not confirmed in the population-based Hungarian case-control study [23].…”
Section: Discussioncontrasting
confidence: 53%
“…In the scientific literatures, there appears to be some conflicting information regarding the safety of multivitamin use in pregnancy. For instance, one study reports that maternal periconceptional intake of vitamin E is associated with congenital heart defects (CHDs), while another study reports that Vitamin E intake during pregnancy does not carry any risk of birth abnormalities . Also, it has been reported that women with excessive serum copper concentrations have a significantly increased risk of having offspring with a CHD, whereas, a low maternal zinc status might have a correlation with CHD .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study reports that maternal periconceptional intake of vitamin E is associated with congenital heart defects (CHDs), 29 while another study reports that Vitamin E intake during pregnancy does not carry any risk of birth abnormalities. 30 Also, it has been reported that women with excessive serum copper concentrations have a significantly increased risk of having offspring with a CHD, whereas, a low maternal zinc status might have a correlation with CHD. 31 In a similar report, it was stated that within the normal range of maternal serum zinc and copper concentrations, there is no variation in risk of neural tube defects but women with very high serum zinc levels may have an increased risk of neural tube defects.…”
Section: The Impact Of Low Iron Intake During Pregnancy and Poor Compmentioning
confidence: 99%
“…e use of vitamin E, although generally considered "healthy," may be harmful to the pregnancy outcome by disrupting the physiological oxidative gestational state and is consequently not recommended to prevent preeclampsia [157]. In a placebo-controlled, doubleblind trial, women diagnosed with chronic hypertension or who had a prior history of preeclampsia who received daily doses of vitamin E (400 IU) and vitamin C (1000 mg) had an increased risk of premature rupture of membranes [203], while another study did not confirm the teratogenic effects of the relatively high-dose vitamin E intake in pregnant women [204]. Further studies are needed on the effect and safety of vitamin E for threatened miscarriage and during early pregnancy.…”
Section: Vitamin Supplementsmentioning
confidence: 99%